2017
DOI: 10.1016/j.jseaes.2017.04.002
|View full text |Cite
|
Sign up to set email alerts
|

An integrated study of geochemistry and mineralogy of the Upper Tukau Formation, Borneo Island (East Malaysia): Sediment provenance, depositional setting and tectonic implications

Abstract: An integrated study using bulk chemical composition, mineralogy and mineral chemistry of sedimentary rocks from the Tukau Formation of Borneo Island (Sarawak, Malaysia) is presented in order to understand the depositional and tectonic settings during the Neogene. Sedimentary rocks are chemically classified as shale, wacke, arkose, litharenite and quartz arenite and consist of quartz, illite, feldspar, rutile and anatase, zircon, tourmaline, chromite and monazite. All of them are highly matured and were derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 91 publications
0
7
0
Order By: Relevance
“…and the Eastern Granite Beltin Peninsular Malaysia (Permian-Triassic), as the age of the zircons (Galin et al, 2017;Nagarajan, Roy, et al, 2017;van Hattum et al, 2013) zircons within the granite found to show that the granitic source could have originated from the Malay Tin Belt during Permian-Triassic (Galin et al, 2017). This inferenceis further strengthened by the geochronology study by Yokoyama, Tsutsumi, and Bong (2015) that dated monazites from the river sands originated turbidites from NW Borneoto be Late Cretaceous to Late Eocene.…”
Section: Possible Source Area and Their Geotectonic Naturementioning
confidence: 90%
See 1 more Smart Citation
“…and the Eastern Granite Beltin Peninsular Malaysia (Permian-Triassic), as the age of the zircons (Galin et al, 2017;Nagarajan, Roy, et al, 2017;van Hattum et al, 2013) zircons within the granite found to show that the granitic source could have originated from the Malay Tin Belt during Permian-Triassic (Galin et al, 2017). This inferenceis further strengthened by the geochronology study by Yokoyama, Tsutsumi, and Bong (2015) that dated monazites from the river sands originated turbidites from NW Borneoto be Late Cretaceous to Late Eocene.…”
Section: Possible Source Area and Their Geotectonic Naturementioning
confidence: 90%
“…Owing to their lower mobility in a variety of environments and lesser residence times in seawater (Cox, Lowe, & Cullers, 1995;Taylor & McLennan, 1985), the trace elements and rare earth elements (REEs) are useful in determining the provenance and tectonic settings. Certain immobile trace elements (e.g., V, La, Th, Zr, Hf, Sc, Co, Ni, Cr, and REEs) are used to identify the most likely provenance of a clastic sedimentary rock (Asiedu, Agoe, Amponsah, Nude, & Anani, 2019;Bhatia, 1985;Bhatia & Crook, 1986;Chen et al, 2019;Cullers, 1995;Cullers & Berendsen, 1998;Cullers & Podkovyrov, 2002;Garver & Scott, 1995;Khan, Sarma, Somasekhar, Ramanaiah, & Ramakrishna Reddy, 2019;Ma et al, 2019;Madhavaraju et al, 2020,b;McLennan, 1989;Nagarajan et al, 2014Nagarajan et al, , 2015Nagarajan et al, , 2019Nagarajan, Armstrong-Altrin, et al, 2017;Nagarajan, Roy, et al, 2017).…”
mentioning
confidence: 99%
“…The overlying Belait Formation and younger sediments of the Miri Zone (e.g. Tukau Formation) also have similar detrital zircon age populations (Hennig‐Breitfeld et al, 2019; Nagarajan et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The CIA values can be also plotted in ternary diagrams (Nesbitt & Young, 1982) such as A‐CN‐K (Al 2 O 3 ‐CaO* + Na 2 O‐K 2 O (Figure 9a) and A‐CNK‐FM (Al 2 O 3 ‐CaO* + Na 2 O + K 2 O‐Fe 2 O + MgO) (Figure 9b) that help interpret the intensity of weathering and provenance. CIA points out the weathering trends of feldspar to clay (Armstrong‐Altrin, Lee, Verma, & Ramasamy, 2004; Fedo et al, 1995; Nagarajan et al, 2017; Nagarajan et al, 2021; Nesbitt & Young, 1982). The CIA values in the range of 80–100 indicate intensive weathering, 60–80 indicate moderate weathering, and <60–50 is considered as the lower intensity of weathering respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Geochemistry of the recent‐ancient clastic sediments/rocks plays an important role in documenting/interpreting the depositional setting, provenance (Bhatia, 1985; Cullers, 1995; Feng & Kerrich, 1990; Nath, Kunzendorf, & Pluger, 2000; Wronkiewicz & Condie, 1990), transport, sorting (McLennan, Hemming, Mcdaniel, & Hanson, 1993; Nesbitt, Young, McLennan, & Keays, 1996), depositional environment (Yan et al, 2007), tectonics (Bhatia & Crook, 1986; McLennan, Taylor, McCulloch, & Maynard, 1990), climate (Ramkumar & Berner, 2015), and weathering (Bhatia & Crook, 1986; Cullers, 1995, Cullers & Podkovyrov, 2000; Mongelli, Cullers, & Muelheisen, 1996; Nesbitt, 2003; Nesbitt & Young, 1982, 1984, 1989;Roser & Korsch, 1986; Taylor & McLennan, 1985) and composition (Condie, 1993; Petersen, Hertle, & SulsbrĂŒck, 2017) of rocks in the source areas and diagenesis (Meng, Wei, Qu, & Ma, 2011; Nagarajan et al, 2017; Pettijohn, Potter, & Siever, 1972; Ramkumar et al, 2018; Roser & Korsch, 1986, 1988).…”
Section: Introductionmentioning
confidence: 99%